Gastric signet-ring cell carcinoma with hypersecretion of β-Human chorionic gonadotropin and review of the literature - Ben Kridis, W.; Ben Hassena, R.; Charfi, S.; Toumi, N.; Boudawara, T.; Khanfir, A.; Frikha, M. (Experimental Oncology, 2018)
β-Human chorionic gonadotropin (β-HCG) is an embryonic protein secreted by the syncytiotrophoblast of the placenta. The determination of the plasma β-HCG level is routinely used for the diagnosis and the follow-up of germ cell tumors. Some adenocarcinomas have been described as being rarely associated with β-HCG hypersecretion. We report a case of gastric signet-ring cell carcinoma with β-HCG hypersecretion and propose hypotheses to explain the pathogenesis of such hypersecretion. Key Words: β-Human chorionic gonadotropin, gastric signet-ring cell carcinoma.